Analysis of the Dynamics of Prices for Shares of Leading IT Companies: IBM, Intel, Apple, Microsoft, Casio Computer Co. - Samorodov, Borys; Zastola, Yevhen; Lyashenko, Vyacheslav (My University, 2023)
Analysis and comparison are research tools that allow you to consider various trends and make the necessary informed decisions. Currently, much attention is paid to IT technologies that contribute to the development of business entities, the introduction of new processes, and the formation of an innovative paradigm. This allows us to talk about the importance of IT companies in the formation of sustainable economic development, relationships between contractors and partners. Most of these companies are listed on the stock market where their securities are located. The display of such an appeal is the dynamics of prices for the relevant shares. The paper considers quotes for shares of leading high-tech companies. To do this, we use standard statistical methods, a quantitative comparison procedure, and wavelet theory. As a result of the analysis, we obtained various dependencies and data estimates, which are presented in the form of stock prices. The findings allow us to understand the dynamics that exist in the IT companies market. We can also develop approaches to the choice of investment strategies when implementing innovative solutions. The article contains many figures and diagrams. This helps to understand the progress of the research.
Keywords: price; dynamics; analysis; stock; comparison; IT-company; securities; stock market; wavelet analysis; wavelet coherence